Profil Proses Estimasi dalam Memecahkan Masalah Numerasi Siswa SMP Berdasarkan Gaya Belajar - Rizal, Muh; Prasetya, Defri Agung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to find the estimation profile in solving junior high school students' numeracy problems based on learning styles. This type of research is descriptive research with a qualitative approach that aims to provide an overview of the estimation process in solving students' numeracy problems based on learning styles. The results of this study indicate that visual learning styles in understanding, planning and implementing problem-solving plans still tend to calculate procedurally and do not utilize estimation strategies. In contrast to auditory learning style subjects in understanding problems, planning and implementing problem-solving plans have used estimation strategies, and in re-checking work, this learning style subject first uses calculations by making scribbles before concluding the truth of the explanation. For kinesthetic learning styles in understanding problems, planning and implementing problem-solving plans have utilized estimation strategies very well in getting their answers. This learning style in getting answers uses more and more varied estimation strategies compared to other learning style subjects. In re-checking the truth of the explanation, this learning style uses more scribbles before concluding the truth of the explanation compared to auditory and visual learning style subjects. In addition, this learning style subject makes good use of the calculation skills that they have to get their answers. In conclusion, learning style is related to the ability to solve numeracy problems, kinesthetic learning style has more answers and varies the use of estimation strategies compared to other learning style subjects Keywords: Estimation, Problem Solving, Learning Styles